Chemical and pharmacological characterization of hypolipidemic compound from Cajanus Cajan (Bangladesh Journal of Pharmacology, 2010)
The study was carried out to identify the compound responsible for hypolipidemic and hypoglycemic effects of Cajanus cajan (redgram). The methanol extract of redgram seeds were fractionated into petroleum ether, chloroform, and methanol.The methanol fraction significantly decreased fasting blood glucose, and lipid profiles (p